Game innovation: a case study using the Kizzugemu visual novel game with Tyranobuilder software in elementary school - Hamidulloh Ibda; Nur Rira Febriani; Muhammad Fadloli Al Hakim; Silviana Nur Faizah; Andrian Gandi Wijanarko; Nanang Qosim (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
This research aims to find out the innovation of the Kizzugemu visual novel game with TyranoBuilder software in elementary school Javanese language learning. The lack of game media innovation in elementary school Javanese language learning is the background of this research. The research method is descriptive and qualitative, with data mining techniques; observation, indepth interviews, and documentation that present the results of descriptions of the innovation, features, application, and impact of using the game in elementary Javanese language learning. The research subjects were the class teacher and 24 fifth-grade students of Madrasah Ibtidaiyah Ma’arif Bulurejo Magelang, Indonesia. The results showed the game’s innovation in multimedia-based game updates, applications, videos, sounds, and texts with the meaning of children’s games in Javanese, Javanese alphabet, Indonesian, and English. Game features are in the form of reading text in each scene and visualized in the material of the Javanese language. The implementation of the game is carried out through five stages which impact teacher awareness, learning media innovation, improved learning outcomes, activeness, understanding of Javanese, and support from parents and schools. Future research needs to explore visual novel game innovation through the latest software.